2019
DOI: 10.1002/mrd.23174
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic markers of low and high fertility bovine spermatozoa separated by Percoll gradient

Abstract: In the context of artificial insemination, male fertility is defined as the ability to produce functional spermatozoa able to withstand cryopreservation. We hypothesized that interindividual variations in fertility depend on the proportion of the fully functional sperm population contained in the insemination dose. The objective of this study was to identify protein markers of the fully functional sperm subpopulation. Insemination doses from four high‐fertility (HF) and four low‐fertility (LF) bulls with compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 73 publications
5
19
0
1
Order By: Relevance
“…Disruption of spermatogenesis at any stage due to either genetic or environmental interventions may render male sterility and, in humans, accounts for 50% of infertility ( Krausz and Riera-Escamilla, 2018 ; Visser and Repping, 2010 ). Although it is conceivable that synthesis and quality of sperm proteome are relevant to sperm quality and male fertility, little is known about how dynamic proteostasis is achieved and maintained during spermatogenesis ( D'Amours et al., 2019 ; Netherton et al., 2018 ; Schafer et al., 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of spermatogenesis at any stage due to either genetic or environmental interventions may render male sterility and, in humans, accounts for 50% of infertility ( Krausz and Riera-Escamilla, 2018 ; Visser and Repping, 2010 ). Although it is conceivable that synthesis and quality of sperm proteome are relevant to sperm quality and male fertility, little is known about how dynamic proteostasis is achieved and maintained during spermatogenesis ( D'Amours et al., 2019 ; Netherton et al., 2018 ; Schafer et al., 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics is an effective tool for sperm analysis and has been used widely to explore the differential proteins between populations with different fertility levels 43,44 or spermatozoa with different motility 45 . Recent proteomics studies of fresh spermatozoa and resuscitated spermatozoa after freezing have suggested that some sperm proteins are associated with sperm quality, and the loss of these proteins may be responsible for the decrease in fertility in cryopreserved spermatozoa 46‐48 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the structure between poly-Ser and poly-Glu may play a special role in evolution. Moreover, it has been reported that the expression of ARMC3 is significantly increased in highly active sperm ( D’Amours et al, 2019 ), whereas the deletion of exon 11 of the ARMC3 gene may alter the reading frame, leading to premature termination of translation, which causes sperm defects and thus male infertility ( Pausch et al, 2016 ). Interestingly, ARMC3 exon 11 encodes amino acids 476–521 of ARMC3, which are located across the end of the last armadillo repeat sequence ( Figures 1 , 2 ).…”
Section: Characteristic Structures Functions and Evolution Of The Armc Subfamilymentioning
confidence: 99%